PESAN EDUKATIF PADA KOMUNIKASI POLITIK CALEG DALAM MENGANTISIPASI POLITIK UANG DI DESA KOEPISINO KECAMATAN BONEGUNU KABUPATEN BUTON UTARA - Isriani, Isriani; Dilla, Sumadi; Joko, Joko (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2020)
The purpose of this study was to find out the educational message on the political communication of legislative candidates in anticipating money politics. The theory used in this research is the message production theory of the Encoding-Decoding model using three approaches, namely the message content, message objectives, and message objectives. This research uses descriptive qualitative method which is done by purposive sampling this is purposely the informant is determined based on the objectives and needs of the  researcher. With the number of respondents as many as 10 people. The data collected was analyzed using descriptive qualitatis analysis.The results of the study show that educative message on political communication of legislative candidates provide a lot of knowledge to the public to choose candidates for people’s representatives intelligently, namely to choose legislative candidates by not only looking at the financial side, choosing legislative candidates who have experienced and have contributed to society, and appeals to the public not to waste  the voice by handing out the votes  they have. Keywords : educative message; political communication;legislative candicates